A multifunctional cryogel for enhanced angiogenesis and osteogenesis in bone tissue engineering - Su, Shenghui; Yang, Ke; Zeng, Yu; Dong, Xieping (Frontiers in Materials, 2025)
Bone defects exceeding self-repair capacity remain a major clinical challenge, necessitating biomaterial-based strategies for effective regeneration. This study developed a multifunctional cryogel integrating copper-containing mesoporous bioactive glass (Cu-MBG) and bone marrow mesenchymal stem cell-derived exosomes (BMSC-Exos) into a decellularized extracellular matrix (dECM). The cryogel’s physicochemical properties, including structure, morphology, porosity, degradation, and mechanical strength, were characterized, confirming its suitability for bone tissue engineering. In vitro studies demonstrated that Cu-MBG/Exos@dECM enhanced osteogenic differentiation and promoted angiogenesis by releasing bioactive copper ions from Cu-MBG and regulating cell proliferation and differentiation via BMSC-Exos. Additionally, the cryogel provided a biomimetic microenvironment supporting cell adhesion and extracellular matrix remodeling, synergistically promoting bone regeneration. These findings highlight Cu-MBG/Exos@dECM as a promising biomaterial for bone repair, offering an effective and advanced strategy for treating bone defects.